Examen especial al activo corriente en la empresa “GlobaLimpio Cía. Ltda.” de la ciudad de Loja. Periodo 2021. - Seraquive Seraquive, Wilson Patricio (2023)
The Curricular Integration Project titled "Special Examination of Current Assets in the Company 'GlobaLimpio Ltda.' In Loja city. Period 2021" was conducted to achieve the stated objectives, which focused on evaluating the Internal Control System of Current Assets in order to determine its level of solidity, administrative efficiency, reasonableness of balances in the 2021 financial statements, compliance with applicable legal and regulatory provisions regarding the registration and control of Current Asset transactions, and the preparation of the Special Examination report that enables executives to make timely and informed decisions for the benefit of the company. The research work was carried out through the three phases of the Special Examination, as well as the preliminary planning that includes general information about the company and its main activities. The specific planning allowed for evaluating and assessing the level of risk and confidence in the company. During the Execution phase, tests and procedures were applied to the accounting records, considering the specific item for analysis, and obtaining results that were documented as findings. In the final phase, Results Communication, an audit report was prepared, presenting the results along with their respective conclusions and recommendations. Among the main findings identified, it was determined that in the company GlobaLimpio Ltda., there is a lack of established policies to safeguard collections, absence of credit policies for the sale of services or materials, inadequate personnel selection for proper warehouse management, delayed deposit of collected funds exceeding 24 hours, and absence of policies for debt recovery. It is noteworthy that the examined item demonstrates a reasonable presentation of its balances.